Experts teachers’ point of view on mathematics teachers’ readiness in becoming professional teachers - Abu Talib, Sharida; Mohamad Nasri, Nurfaradilla; Mahmud, Muhammad Sofwan (Journal of Education and Learning (EduLearn), 2025)
Today’s educational changes necessitate that teachers have a broad range of knowledge, values, skills, and competencies to provide effective instruction. Despite this, research on mathematics teachers’ readiness for such changes is limited, particularly in terms of leveraging experienced teachers’ implicit knowledge for peer learning. This qualitative exploratory study delves into the perceptions and factors influencing mathematics teachers’ readiness for educational changes, as reported by four expert teachers. Note that data was collected through semi-structured interviews and analyzed thematically with Atlas.ti 23 software to identify key themes and subthemes. The findings reveal that all experts emphasized the importance of professionalism in teaching mathematics, with pedagogical challenges taking priority. The main challenges include mastering teaching skills, which are critical to teacher readiness. Consequently, the study concludes that improving teacher readiness necessitates specific support and focused programs. This highlights the importance of a comprehensive model that addresses the pedagogical needs of mathematics teachers, who play a critical role in change. Further research should focus on investigating mathematics teachers’ readiness in a broader context, emphasizing their professional knowledge and pedagogical skills.